Introduction to marketing - McDaniel, Carl; Lamb, Charles W.; Hair, Joseph F. (South-Western/Cengage Learning, 2013)
Offers students the ability to recognize how much marketing principles play a role in their day-to-day lives. This title enables students to experience marketing through billboards, television commercials, and in the cereal aisle at the grocery store.